A clinical study on congenital diaphragmatic hernia in neonates: Our institutional experience - Jayalaxmi Shripati Aihole; Aruna Gowdra; Deepak Javaregowda; Vinay Jadhav; M Narendra Babu; Ravidra Sahadev (Wolters Kluwer Medknow Publications, 2018)
Background: Congenital diaphragmatic hernia (CDH) is a complex developmental defect having a multifactorial etiology; i majority of cases (~80%), the cause is not known. Survival rates for patients with CDH have increased over the past decade with early prenatal detection and better postnatal management including surgery. Clinical profile and the outcome of 83 CDH neonates were studied and analyzed over a period of 12 years in our institute. Aims and Objectives: The clinical study was to analyze the clinical profile and outcome of CDH among the neonates in a tertiary care referral neonatal and pediatric center in Karnataka, India. Materials and Methods: This was a retrospective and prospective observational study conducted from January 2005 to March 2017, over a period of 12 years in a tertiary care referral neonatal and pediatric center in southern India. Clinical characteristics and risk factors of 83 neonates admitted and diagnosed with CDH were compared between survivors and nonsurvivors both preoperatively and postoperatively. Neonates with clinical and intraoperative diagnosis of diaphragmatic eventration were not included in this study. Multivariate logistic regression analysis was performed to determine independent predictors for mortality. Results: A total of 83 neonates admitted and diagnosed with CDH were included in this study; 73 of them underwent surgical repair. The total survival rate in neonates with CDH was 70/83 (84.33%) and the overall operative mortality was 3/73 (4.1%). There was a significant difference between CDH neonates who survived 70/83 (84.33%) and those who died 13/83 (15.67%), in the age on admission, 5 min Apgar score, onset of respiratory distress, preoperative ventilation, the presence of persistent pulmonary hypertension of the newborn (PPHN), high-frequency oscillatory ventilation (HFOV), and length of hospital stay with P < 0.05. Using multivariate logistic regression analysis, the following factors independently predicted mortality: onset of respiratory distress in hours (odds ratio: 0.5, 95% confidence interval: 0.37-0.82) and preoperative ventilation (odds ratio: 0.02; 95% confidence interval: 0.0028-0.1558). When we compared CDH neonates who survived after surgery (n = 70) with those who expired (n = 3) postoperatively, there was a significant difference in the gestational age in weeks, side of CDH, PPHN, HFOV and length of hospital stay with P < 0.05. Conclusion: CDHs are common on the left side with fairly good prognosis. Though, the right-sided CDH are rare; they do carry a good prognosis, as it was seen in our experience.